Religiosity and Stress on Nurses during COVID-19 Pandemic at a Hospital in Bandung - Siska Nia Irasanti; Rizki Perdana; Dhian Indriasari; Yuniarti Yuniarti; Ahmad Kamil; Wellisna Merduani (Universitas Islam Bandung, 2022)
The problem of the coronavirus disease 2019 (COVID-19) pandemic has resulted in changes in various aspects of life, primarily related to health services. All health workers involved in handling COVID-19 are likely to experience psychological pressure in treating COVID-19 patients with an increasing number of patients. The correlation between religiosity is expected to guide an individual in interacting in the work environment, including in health services and managing stress on nurses. This study aimed to analyze the correlation between religiosity and stress at work during the COVID-19 pandemic in nurses. This research is an observational analytic with a cross-sectional approach. Primary data was obtained from a questionnaire to 78 nurses in the COVID-19 ward at a hospital in Bandung in August 2021. The Pearson correlation test analysis results showed a significant correlation between religiosity and stress. Religious maturity can influence a person's level of mental maturity. It can give a feeling of peace in the heart so that a person can avoid feeling restless and anxious about the problems faced without stress.